FTIR Studies of Ethanolic Extract of Diascorea bulbifera IFERA - Jyothi, Asha (International Journal of Pharmaceutical & Biological Archive, 2016)
FTIR Studies of Ethanolic Extract of Diascorea bulbifera IFERA